SNACK FOOD CONSUMPTION BEHAVIOR AMONG STUDENTS OF SDN 51 JAYA BARU BANDA ACEH - Nuraini, Aruna; Laweung, Ibrahim; Ramadhaniah, Ramadhaniah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Elementary school students are prone to consuming snacks due to the variety of options available at school. Although common, there is limited research examining the factors influencing snack consumption behavior among children in Banda Aceh. Objective to identify factors associated with snack consumption behavior among students at SDN 51 Jaya Baru, Banda Aceh City. Method: This study used a descriptive-analytic design with a cross-sectional approach. A total of 69 students were selected through total sampling. Data were analyzed using the chi-square test with STATA 13 software. Result: Significant relationships were found between snack consumption behavior and knowledge (p0.013), peer influence (p=0.003), advertising (p=0.025), and the habit of bringing lunch (p=0.037). No significant relationship was found with pocket money (p=0.168). Recommendation: Schools are encouraged to collaborate with health workers to provide education on the risks of unhealthy snack consumption.